Analisis Karakteristik Rewetting Dalam Celah Sempit Vertikal Untuk Kasus Bilateral Heating Berdasarkan Perubahan Temperatur Awal Plat - Catrawedarma, IGN. Bagus; -, Indarto; Juarsa, Mulya; Handoyo, Ismu; -, Kiswanta; Fitriana, Ririn (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011)
Boiling heat transfer to analysis of effect main plate initial temperature to rewetting characteristics that arerewetting time, and pattern of rewetting were studied from transient temperature of surface plate. It is as result of experimentusing two vertical plate with 1 mm narrow gap. Debit and temperature of cooling water were controlled about 0,09 lt/s andsaturated temperature. The initial temperatures of main plate were changed from 500°C, 550°C, and 600°C. As results shownthat midle part of main plat has the highest value of rewetting time that is 310 second at 600°C initial main platetemperature, the lowest rewetting time is 40 second at 500oC initial main plate temperature on the bottom part of plate. Thehigher the plate initial temperature, the longer the rewetting time and variation of the plate initial temperatures can notinfluent the pattern of rewetting.
Keywords: rewetting time, pattern of rewetting.